CABI Compendium 2016
DOI: 10.1079/cabicompendium.24010452
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Systems for Horticulture

Abstract: This datasheet on Decision Support Systems for Horticulture covers Identity, Overview, Description, Further Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Annual financial results are maximized by making optimal choices from alternatives for structure types, covering material, shade screening, whitewash, thermal screens, heating and cooling systems, and CO 2 enrichment. Further research on this topic can be found in the efficient land use planning section presented by Mir and Padma [7]. As shown in our exploratory study, strategic production design requires the consideration of a vast number of additional factors in practice.…”
Section: Pertinent Literature and Gapsmentioning
confidence: 86%
See 3 more Smart Citations
“…Annual financial results are maximized by making optimal choices from alternatives for structure types, covering material, shade screening, whitewash, thermal screens, heating and cooling systems, and CO 2 enrichment. Further research on this topic can be found in the efficient land use planning section presented by Mir and Padma [7]. As shown in our exploratory study, strategic production design requires the consideration of a vast number of additional factors in practice.…”
Section: Pertinent Literature and Gapsmentioning
confidence: 86%
“…Based on the results of our literature research, so far only Mir and Padma [7] presents an overview of different decision support systems in a horticultural context. They review multiple plant-specific contributions for general purposes in horticulture and applications for integrated plant protection, nutrient management, and land use.…”
Section: Literature Overview and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It accounts for over 67.7% of the country’s total apple production 1 . The area under fruit cultivation in the study area is 0.333 M ha (2020 to 2021), where the highest average apple production was recorded in the Baramulla district (439 thousand MT) during 2016 to 2020 2 . The horticultural sector in the Kashmir Valley contributes over 27% to the region’s economy 3 .…”
Section: Introductionmentioning
confidence: 97%